Enhancing Employee Performance through Organizational Citizenship Behavior: A Study on the Impact of Organizational Commitment and Work Motivation - PUTRA, I Kadek Yogik Dharma; GAMA, Agus Wahyudi Salasa; ANGGRAINI , Ni Putu Nita (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose:This research investigates the mediating role of Organizational Citizenship Behavior (OCB) in the relationship between organizational commitment, work motivation, and employee performance at Eden Hotel Kuta Bali. Specifically, the study aims to assess how organizational commitment and work motivation influence employee performance directly and indirectly through OCB, thereby providing insights into strategies for improving employee performance and achieving organizational goals in the hospitality industry. Methodology:This research utilizes a quantitative approach to examine the impact of organizational commitment and work motivation on employee performance, with organizational citizenship behavior (OCB) serving as an intervening variable at Eden Hotel Kuta Bali. The study's population includes all 106 Eden Hotel Kuta Bali employees, with a census. Inferential Analysis: Employs Structural Equation Modeling (SEM), specifically Partial Least Squares (PLS), to test the empirical model and hypotheses proposed in the study. Findings:The results of this study indicate that among the three variables examined for their impact on employee performance, organizational commitment, work motivation, and organizational citizenship behavior all have a positive and significant effect on employee performance at Eden Hotel Kuta Bali. Employee performance is also expected to increase as organizational commitment, work motivation, and organizational citizenship behavior improve. Implication:This research indicates that organizational commitment, work motivation, and organizational citizenship behavior all positively and significantly impact employee performance at Eden Hotel Kuta Bali. Additional studies will help identify and understand other aspects influencing employee performance in a broader context, providing deeper insights into the factors contributing to improved employee performance across various organizational settings